Film censorship in Malaysia: balancing free speech and tradition - Shuaib, Farid Sufian; Islam, Md Zahidul (2014)
Freedom of speech is the freedom to speak freely without censorship or limitation. Freedom of speech is a fundamental to the existence of democracy and the respect of human dignity. The making and exhibition of films also falls under the free speech clause. Similar to other fundamental liberties, free speech is not absolute and subject to reputation of others, national security, public health and morals. The Malaysian Film Censorship Board have embroiled in controversy when they censored and banned several films on the ground of public order, morals and religious sensitivities such as Tanda Putera, Sepet, Dalam Botol and The New Village. The importance of tradition that consists of morals and religious values could not be summarily dismissed because of its constitutional standing and societal significance. Thus, these tensions between competing interests should be analysed so that a logical framework could be established in film censorship. This paper discusses the legal framework of film censorship and explains film censorship guidelines as adopted by the Film Censorship Board. The place of moral and religious values and the competing interests of free speech in this censorship framework is analysed.